Mechanical Performance of Sustainable Bio-Based Compounds - Acierno, Domenico; Patti, Antonella (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue collected original contributions, both research papers and reviews, showing recent results and/or positive advances in the behavior of new sustainable bio-materials under applied mechanical stress, both in static and dynamic mode, and evaluating the characteristics of resistance, moduli and/or viscoelasticity, in view of potential applications, such as tissue engineering, medical devices, surgical or dental implants, manufacturing of human parts, agriculture, packaging, textiles, electronics, automotive and aerospace, green buildings, and architecture and construction.